Sedimentation Field-flow Fractionation in Thin Channels and Rotating Coiled Columns: From Analytical to Preparative Scale Separations. Issue 4 (2nd October 2021) - Ivaneev, Alexandr I.; Ermolin, Mikhail S.; Fedotov, Petr S.; Faucher, Stéphane; Lespes, Gaëtane
ABSTRACT: Theoretical background, instrumentation, and applications of "conventional" sedimentation field-flow fractionation in thin channels (SdFFF) and "non-conventional" sedimentation coiled-tube field-flow fractionation (CTFFF) in rotating columns are summarized and compared. Applications are classified into three main groups: environmental studies, material science, and biological studies. SdFFF is a versatile separation and sizing method applicable to complex particulate matter such as environmental samples, engineered particles, cells, etc. However, the mass of injected particles does not usually exceed 10–20 µg to avoid overloading. CTFFF enables the mass of the particulate sample to be increased up to grams. Despite its low resolution as compared to SdFFF, CTFFF has important niche applications. It opens a new door into the isolation of nano- and submicron particles from bulk samples of different origin and nature. In addition, CTFFF is a very promising instrument for the separation and purification of nano- and microparticles at preparative and even industrial scale. Abbreviations: A4F – Asymmetrical flow field-flow fractionation; CSF – Conventional SPLITT fractionation; CTFFF – Coiled-tube field-flow fractionation; CV-ETAAS – Cold vapor electrothermal atomic absorption spectroscopy; DLS – Dynamic light scattering; EDS – Energy dispersive X-ray spectroscopy; ES-SMPS – Electrospray-scanning mobility particle sizer; ETAAS – Electrothermal atomic absorption spectroscopy; FE – Fractionation efficiency; FFDSF – Full feed depletion SPLITT fractionation; FFF – Field-flow fractionation; ICP-AES – Inductively coupled plasma-atomic emission spectrometry; ICP-MS – Inductively coupled plasma-mass spectrometry; LD – Laser diffraction; MAD – Monoolein aqueous dispersions; MALS – Multi-angle light scattering; NLC – Nanostructured lipid carriers; NP – Nanoparticle; NTA – Nanoparticle tracking analysis; OM – Optical microscopy; PS – Polystyrene; PSD – Particle size distribution; RCC – Rotating coiled column; SdFFF – Sedimentation field-flow fractionation in thin channels; SEM – Scanning electron microscopy; SP-ICP-MS – Single-particle inductively coupled plasma-mass spectrometry; SPLITT – Split-flow thin-cell fractionation; TEM – Transmission electron microscopy; UV – Ultraviolet detector